Temperature controlled infrared drying kinetics of mussels - Sevim, Sema; Derun, Emek; Tugrul, Nurcan; Doymaz, Ibrahim; Kipcak, Azmi Seyhun (SCIENTIFIC PUBL-INDIA, 2019)
Mussel has impressive nutritional values, which contains many vitamins, minerals and proteins by comparison with other shellfish. Infrared drying (IR) has,gained popularity in the food industry due to its rapid drying rate/response time and superior thermal efficiency compared to traditional drying methods for the recent years. In this study, various temperatures (60, 70 and 80 degrees C) were applied to mussels via infrared dryer to investigate the temperature effect on drying characteristics, effective moisture diffusivity and activation energy. The drying times are obtained as 405, 255 and 165 min for 60, 70 and 80 degrees C, respectively. Drying temperature at 80 degrees C was found as the optimum temperature in the experiments for quality of mussel and energy consumption. To identify the drying kinetic of mussel, seven mathematical models were applied to the experimental results and Alibas model provided to best estimation for each temperature according to drying data. The results are found as 0.999886, 0.999916 and 0.999964 for coefficient of determination (R-2); 0.000011, 0.000009 and 0.000006 for reduced chi-square (chi(2)) and 0.002946, 0.002614 and 0.001854 for root mean square error (RMSE) at 60, 70 and 80 degrees C, respectively. Effective moisture diffusivity values are found as 4.23x10(-9), 7x10(-9) and 1.17x10(-8) m(2)/s at 60, 70 and 80 degrees C, respectively. It is clearly seen that the effective moisture diffusivity values increased with temperature increment. The effect of temperature on the moisture diffusivity depends on Arrhenius equation. According to the relationship 49.67 kJ/mol is calculated as an activation energy of mussel.
Keywords: Mussel; infrared radiation; drying kinetic; mathematical modelling; activation energy; Chemistry